Kuliah Kerja Nyata: Sosialisasi Pentingnya Lanjut Pendidikan Di SMP 10 Nopember Binangun Kabupaten Cilacap Sebagai Upaya Mengurangi Siswa/i Putus Sekolah - A Rahmadian; D J Barokah; Faiza Akmala; L Hidayah; R S Herdanty; , R A G Prawadya; R M Lestari; S N Praresanti; V R Illahi; V B T Tambunan (Universitas Madako Tolitoli, 2026)
A socialization program on the importance of continuing education was held at SMP 10 November, Binangun Subdistrict, Cilacap Regency, aiming to prevent school dropouts. This initiative was motivated by the low average years of schooling in Cilacap (7.39 years) and the high number of students who only completed basic education. The program was conducted by KKN students of Universitas Jenderal Soedirman using a qualitative descriptive method through material presentation, interactive discussions, reflective writing, and ice-breaking sessions designed to motivate students in planning their future. The results showed strong enthusiasm, demonstrated by active participation and willingness to share aspirations. The program increased students’ awareness of education as a long-term investment for personal development and family welfare. It also identified real challenges such as economic limitations and school distance while offering practical solutions such as scholarships and family support. Overall, this program effectively fostered students’ motivation to pursue higher education and contributed to reducing dropout rates in Cilacap. Keywords: Education, Dropout, Socialization, Learning Motivation, Cilacap